Cajaninstilbene acid inhibits osteoporosis through suppressing osteoclast formation and RANKL‐induced signaling pathways. Issue 7 (4th December 2018) - Sun, Youqiang; Liu, Yuhao; He, Wei; Wang, Chao; Tickner, Jennifer; Kuek, Vincent; Zhou, Chi; Wang, Haibin; Zou, Xuting; Hong, Zhinan; Yang, Fan; Shao, Min; et al.
Abstract: Osteoporosis is a form of osteolytic disease caused by an imbalance in bone homeostasis, with reductions in osteoblast bone formation, and augmented osteoclast formation and resorption resulting in reduced bone mass. Cajaninstilbene acid (CSA) is a natural compound derived from pigeon pea leaves. CSA possesses beneficial properties as an anti‐inflammatory, antibacterial, antihepatitis, and anticancer agent; however, its potential to modulate bone homeostasis and osteoporosis has not been studied. We observed that CSA has the ability to suppress RANKL‐mediated osteoclastogenesis, osteoclast marker gene expression, and bone resorption in a dose‐dependent manner. Mechanistically, it was revealed that CSA attenuates RANKL‐activated NF‐κB and nuclear factor of activated T‐cell pathways and inhibited phosphorylation of key signaling mediators c‐Fos, V‐ATPase‐d2, and ERK. Moreover, in osteoclasts, CSA blocked RANKL‐induced ROS activity as well as calcium oscillations. We further evaluated the therapeutic effect of CSA in a preclinical mouse model and showed that in vivo treatment of ovariectomized C57BL/6 mice with CSA protects the mice from osteoporotic bone loss. Thus, this study demonstrates that osteolytic bone diseases can potentially be treated by CSA. Abstract : Cajaninstilbene acid (CSA), a natural compound derived from pigeon pea leaves, has the ability to suppress RANKL‐mediated osteoclastogenesis, osteoclast marker gene expression, and bone resorption in a dose‐dependent manner. It attenuates RANKL‐activated NF‐κB and nuclear factor of activated T‐cell (NFAT) pathways and inhibited phosphorylation of key signaling mediators c‐Fos, V‐ATPase‐d2, and ERK. Moreover, in osteoclasts, CSA blocked the RANKL‐induced ROS activity as well as calcium oscillations.The treatment of ovariectomized C57BL/6 mice with CSA protects the mice from osteoporotic bone loss. Thus, this study demonstrates that osteolytic bone diseases can potentially be treated by CSA.